THE CHANGING ROLES OF THE STATE IN SHRIMP FARMING GOVERNANCE IN THE MEKONG DELTA, VIETNAM - Thi Thu Ha, Tran (Journal of Forestry Science and Technology, 2016)
The paper highlights two key transformations in the governance of Vietnamese shrimp aquaculture in the Mekong Delta and the changing roles of the state in the context of emergent concerns about environmental and social impacts of shrimp farming in the tropics. The first transformation is an extended period of growth and expansion and top-down approach to regulation of this sector. The second transformation is also in response to market demands but is directed to the emergent ‘quality’ concerns about the environmental and social impacts of shrimp farming. Our results indicate that this second governance shift has created a new set of challenges for the Vietnamese government, which, within the context of global market, is now promoting regulation of environmental quality through third-party certification as a market-based and farmer cluster practices as community-based mechanisms. To overcome these challenges, the Vietnamese government should change itself from a regulator to a facilitator of global governance arrangements, especially as farmers and global market actors are engaged in transnational regulatory networks operationalized at local scales.